Navigating Belonging While Experiencing Discrimination: Migrant Women’s Aspirations in Norway’s Labour Market - Amanda Miriam Tallis (Genealogy)
This article examines how belonging and aspirations among women with a migrant background are shaped by experiences of discrimination in the Norwegian labour market. While extensive research exists on policy implementation and public measures aimed at integrating migrants into the labour market, less focus has been placed on understanding how migrants’ work aspirations and desires are shaped. This article builds on ethnographic fieldwork conducted among migrant women in a Norwegian city. Drawing on research suggesting that migrants’ agency is influenced by actual or perceived opportunity structures, I explore how discrimination, as a distinct structural barrier, (re)shape aspirations and belonging among women with migrant backgrounds. In this article, I explore identity and belonging as dynamic and context-dependent, rather than fixed categories like gender, ethnicity, or class. The findings show that discrimination is a salient part of women’s experiences in the labour market and further illustrate how discrimination affects their sense of belonging, and their aspirations connected to work-life. Some women seek belonging in arenas other than the labour market in society, where they experience that their resources are valued.